Seronegative chronic polyarthritis: clinical and serological correlates. Issue 6 (December 1980) - Rasker, J L; Davis, P; Bacon, P A
Abstract : Twenty-seven patients with chronic, active, seronegative polyarthritis were assessed clinically and serologically by accepted criteria for evidence of connective tissue diseases. The patients were divided into 2 groups, 13 positive for fluorescent antinuclear antibody (FANA) and 14 that were negative. All but 1 patient fulfilled the clinical criteria for the diagnosis of definite rheumatoid arthritis. Four patients (2 in each group) fulfilled the preliminary criteria for the classification of systemic lupus erythematosus. Antiperinuclear factor was positive in 5 of the FANA-negative patients, consistent with a diagnosis of rheumatoid arthritis. By contrast, this factor was absent in all the FANA-positive patients. Positive DNA binding was found in 7 of the FANA-positive patients, in high titre in 4, consistent with a diagnosis of 'minimal lupus' with predominantly 'unisystem' disease. DNA binding was positive in low titre in 2 of the FANA-negative patients. Antibodies to extractable nuclear antigens (ENA) were found in 4 patients with a positive FANA and in only 1 FANA-negative patient. The current clinical criteria showed poor discriminatory value in classifying cases of seronegative polyarthritis, which may represent mild cases of other connective tissue disease presenting with synovitis in the absence of extra-articular disease manifestations.